2017
DOI: 10.11114/jets.v5i5.2310
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Of Students In Physical Education and Sports College and The Students In Other Departments In Terms Of Problem Solving Skills

Abstract: In this research, it is aimed to analyze the problem solving skills of university students in terms of different variables and to analyze the differences among the levels of perceived problem solving skill of the students of Physical Education and Sports College and other branch students. The sample consists of the university students from the School of Physical Education and Sports (128) and from the Department of Tourism and Hotel Management (104) from the Faculty of Economics and Administrative Sciences Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, in the case of factor 2, the treatment exhibited positive effects exclusively among chemistry students, manifesting as an improved subjective rating in establishing evaluation criteria, empathizing with others, and effectively weighing and prioritizing various arguments. The unexpected reduction in factor 2 among sports and health students may be attributed to the treatment's emphasis on problem complexity [72]. At this juncture, the education department effect, which describes students' thinking in accordance with the educational outcomes of their education departments has shown effects., e.g., on creative thinking [73], and could provide further explanation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of factor 2, the treatment exhibited positive effects exclusively among chemistry students, manifesting as an improved subjective rating in establishing evaluation criteria, empathizing with others, and effectively weighing and prioritizing various arguments. The unexpected reduction in factor 2 among sports and health students may be attributed to the treatment's emphasis on problem complexity [72]. At this juncture, the education department effect, which describes students' thinking in accordance with the educational outcomes of their education departments has shown effects., e.g., on creative thinking [73], and could provide further explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Nopembri et al (2019) found that students can effectively improve their ability to cope with stress and solve problems in physical exercise by participating in activities that need critical thinking, inquiry, and cooperation with others. According to Görücü and Cantav (2017), problem solving is one of the most basic skills that physical education majors and students in sports colleges and universities should master, and the ability to solve problems is considered an important factor for athletes' success. Although some problems have clear solutions or correct answers, others do not, and solving them requires interdisciplinary knowledge, comprehensive thinking, and creativity (Steiner & Posch, 2006).…”
Section: Problem-solving Abilitymentioning
confidence: 99%
“…Problem solving is a method, a procedure, and an attempt to recognize, explain, assess, and resolve a gap between a preexisting condition and a goal (Khan et al, 2016). Empirical research systematically reports gender differences in problemsolving process, style, and skill (Burnett et al, 2016;Ekici, 2016;Görücü & Cantav, 2017;Hardy & Gibson, 2015). Specifically, women were found exhibiting greater levels of creative problemsolving (Hardy & Gibson, 2015) and positive perceptions of the general problem-solving process (Ekici, 2016).…”
Section: Women's Problem Solvingmentioning
confidence: 99%
“…The finding was also confirmed in Khan et al's (2016) recent research on university students' problem solving style. Notice that, because many empirical research in problem-solving was conducted on students at high school (Ekici, 2016;Hoogerheide et al, 2016) and university levels (Görücü & Cantav, 2017;Keener & Strough, 2017;Khan et al, 2016), the application of these scientific findings on professional women workers in leadership positions may require further investigation. Women workers may have different leadership traits and behaviors from women students.…”
Section: Women's Problem Solvingmentioning
confidence: 99%